Exploring the role of innovation in enhancing mathematics achievement in higher secondary students - Janardhanan, Jayalekshmi; Charles, M. Aron Antony (Edelweiss Applied Science and Technology, 2024)
Mathematics is an essential part of education, important for students’ intellectual development and practical application in daily life. Innovative techniques, such as technology integration and project-based learning, are increasingly recognized for improving students’ engagement and academic achievement in mathematics. This study examines the effectiveness of modern techniques on the mathematics achievement of higher secondary students in selected schools in Kerala. Using a mixed-methods approach, data were collected from 300 students through interviews, surveys, and classroom observations. The study analyses the factors such as parental involvement, curriculum design, peer interaction, and the availability of technological infrastructure. Statistical tools such as Chi-square tests, ANCOVA, linear regression, and hierarchical regression were utilized to analyze the relationships between these variables and students’ academic performance. Results indicate that students exposed to interactive, technology-enhanced lessons demonstrate significant improvements in mathematical achievement. Peer collaboration and high parental involvement positively influence academic outcomes, while access to technological resources enhances learning. Students with lower math anxiety and higher self-efficacy also show greater academic improvements. The study concludes that innovative methods, when combined with supportive learning environments and reduced anxiety levels, significantly improve students’ mathematics performance, emphasizing the importance of active participation and modern resources in education.